The Effect of Traditional Drying on Salted Fish Quality - Mira, Mira; Windari, Sulis; Reski, Seri Mulia; Hakiki, Ismi Della; Ishak, Khardianti Alviani; Putri, Lidya Oktavia; Marta, Eni (International Journal of Natural Science and Engineering, 2022)
Fish is a source of animal protein that is widely consumed by the public. With a high protein content, fish quickly undergo a post-harvest decay process if it is not directly processed into food. In general, what causes fish to rot quickly are bacterial and chemical factors. as for the method used in this study is a qualitative research approach. The purpose of this study was to determine the effect of drying on the quality of fish. The results showed that the drying time of fish depends on the weather and also the size of the fish. Drying using sunlight is widely used because heat energy is abundant and the equipment used is inexpensive. during the drying process cleanliness must be monitored. This study also aims to determine the difference between drying fish using salt and not using salt. The parameters observed were the quality of the fish starting from the texture, color, smell, and content contained in the fish after drying. Drying salted fish is widely available in Indonesia, on a national scale salted fish is one of the fishery products that has an important position. The technique of drying salted fish using sunlight is a common technique carried out in Indonesia with the position of the fish being hung and then placed outside or under the sun.